Wong's essentials of pediatric nursing - Wilson, David; Upchurch, Sandra L.; Brosman, Christine A.; Barrera, Patrick; Hockenberry, Marilyn J.; Gallagher, Martina (Elsevier, 2013)
Wong’s Essentials of Pediatric Nursing has been a leading book in pediatric nursing since it was first published more than three decades ago. This kind of support places a unique accountability and responsibility on us to earn your future endorsement with each new edition. So, with your encouragement and constructive comments, we offer this extensive revision, the ninth edition of Wong’s Essentials of Pediatric Nursing